التناص عند محمد القيسي وتاثره فيدريكو غارسيا لوركا الإسباني - قوعيش, سهام (كلية الأدب العربي والفنون, 2024)
يعتبر محمد القيسي من بين الشعراء الفلسطينيين الذين ضحوا بحياتهم مسخرين القلم لدفاع عن القضية الفلسطينية وأعمال الترجل شاهدة على ذلك حيث تمير بثقافته الواسعة واطلاعه على الآداب العربية والغربية بصفة كاملة كان شعره منبر لسماع صوته وتبليغ رسالته، وخير من تأثر بأعمالهم الشاعر الإسباني فیدريکو غارسیا لوركا الذي زاد في ثقافته، وتأثر بأعماله فاكتسى طابع الحزن والاغتراب عن وطنه كما أنه وظف الكثير من الرموز الدالة على لوركا سواء في الأماكن أو الكلمات ليوصل بذلك فكرته للقارئ Muhammad Al-Qaisi is considered among the Palestinian poets who sacrificed their lives, using the pen to defend the Palestinian cause, and his poetic works are a witness to this, as he is distinguished by his vast culture and his complete knowledge of Arab and Western literature. His poetry was a platform for hearing his voice and conveying his message. The best person influenced by their works was the Spanish poet Federico Garcia Lorca, who He increased his culture, and was influenced by his works, so he took on a character of sadness and alienation from his homeland. He also employed many symbols indicating Lorca, whether in places or words, to convey his idea to the reader
Keywords: ماهية التناص - أثر لوركا في الشعر العربي الحديث - أنواع التناص عند القيسي - تأثر القيسي بشعر لوركا; The nature of intertextuality - Lorca’s influence on modern Arabic poetry - Types of intertextuality according to Al-Qaisi - Al-Qaisi’s influence on Lorca’s poetry